Evaluating the inactivation of a surrogate ASFV-like algal virus in a pilot solvent extraction soybean processing facility - Amanda Palowski; Cecilia Balestreri; Pedro E. Urriola; Jennifer L. G. van de Ligt; Richard Ozer; Gerald C. Shurson; Declan C. Schroeder (Frontiers in Animal Science)
IntroductionAfrican swine fever virus (ASFV) is extremely stable in the environment, and previous laboratory experiments and simulations have also shown it to be highly stable in animal feed ingredients. However, ASFV cannot be studied in real world demonstrations because it is a highly contagious virus. African swine fever virus is a member of the nucleocytoplasmic large DNA viruses (NCLDVs), and similar to Emiliania huxleyi virus (EhV), which has a restricted host range limited to a species of marine algae called Emiliania huxleyi. This algal NCLDV has many similar morphological and physical characteristics to ASFV, thereby making it a safe surrogate for generating experimental results that are applicable to ASFV and representative of real-world conditions. MethodsWe inoculated whole soybeans with EhV strain 86 (EhV-86) at a concentration of 1.80 × 108 virus/mL, which were then processed at a pilot solvent extraction facility to produce soybean hulls and meal. After processing, samples were evaluated for virus presence and viability using a previously validated viability qPCR (V-qPCR) method.ResultsNo detection of EhV-86 occurred on environmental surfaces, air, and dust samples pre- or post-processing. Viable EhV-86 was detected in conditioned soybeans, dehulled soybeans, soybean hulls, soybean flakes, air-dried solvent extracted soybean flakes, post-desolventizer toaster soybean flakes, and soybean meal after reaching steady state during solvent extraction processing.DiscussionIt is important to note that 95% of viable virus was recovered (2.43 × 106 virus/g in replicate A and 2.61 × 106 virus/g in replicate B) in soybean meal, suggesting that longer retention times or application of chemical mitigants may be needed for more complete inactivation. The high concentration of viable viruses remaining on the soybean hulls after processing (1.98 × 107 virus/g in replicate A and 2.12 × 107 virus/g in replicate B) is a major concern for potential virus transmission in animal feed. These results demonstrate for the first time that ASFV-like NCLDVs can retain viability in soybean hulls, flakes, and meal during solvent extraction processing in a pilot facility and remain a hazard for virus transmission. Future risk assessments focused on the role of contaminated feed ingredients in transmission of viruses to swine farms must consider the ingredient composition of complete feeds delivered to farms and the initial concentration of viable viruses.